Anglophone Poetry in Kenya at the Turn of the Century: Past Experience and Artistic Transformation - N. S. Frolova (Научный диалог)
The main trends in the development of the English-language poetry of Kenya at the turn of the XX—XXI centuries are considered. The main material is a collection of poems by Kenyan poets, first published in the early 2000s. Particular attention is paid to the ideological and artistic transformation in the work of the young generation of Kenyan poets of the key directions in the development of Kenyan English-language poetry, which developed in the first half of the XX century. The novelty of the research lies in the conclusion about the continuity of the experience of the older generation poets by the English-speaking Kenyan poets, which is expressed in the development of two key directions of the development of Kenyan English-language poetry: socio-political and philosophical-lyric. At the same time, a fundamental change in the artistic method and style transformation is noted in the work of the new generation of Kenyan authors: unlike their predecessors, young Kenyan poets are increasingly gravitating towards the use of rhyme, expressed allegory and imagery, and also adopting previously untested techniques, for example, the use of elements of youth subculture. New material has been brought in, many names are first introduced into the everyday life of domestic and world African studies.